Contributions to the study of adverbial clauses introduced by 'em vez de' in the PEC - Macário Lopes, Ana Cristina (2016)
The aim of this paper is to characterize the subordinate adverbial clauses introduced by ‘em vez de’ in European contemporary Portuguese. In syntactic terms, these clauses are peripheral, loosely linked to the main clause, rejecting all focusing structures. A semantic-pragmatic hypothesis is put into test to explain this behaviour: the information expressed by the adverbial clauses is pressupposed. Two semantic sub-types of ‘em vez de’ clauses are thouroughly described: (i) those which contrast a factual situation with the speaker’s expectation and (ii) those which contrast a factual situation with a non-factual preferential alternative. A fine-grained analysis of the modal values involved is carried out, and, in a smaller scale, temporal and aspectual values are also taken into consideration.